Social Sciences and Big Data: Platforms and Challenges - Seminario Córdova, Renzo Antonio (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
The objective of this research was to explore and characterize the main big data repositories in the area of ​​social sciences available in 2021. The research design was non-experimental, exploratory and descriptive. The population consisted of 110 big data located by the Google dataset search engine. The sample corresponded to the top 10 big data. The results indicated that the most important big data repositories and platforms are centralized by the private sector located in US companies, fundamentally.